ENGLISH LEARNING USING NATURE-BASED LEARNING METHODS TO INCREASE STUDENT MOTIVATION - Palupi, Muji Endah; arfani, Sri (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2023)
The purpose of this research is to study English learning using nature-based learning methods to increase students' motivation in learning. In the minds of some students there is still a paradigm that assumes that success in learning English is due to talent. This assumption encourages students to be lazy to learn English. They tend to be more desperate and give up when they encounter difficulties in learning. However, learning English can be done anywhere and anytime using any method. The goal is that students can be motivated to develop learning that is more interesting and has a positive impact. The learning environment makes students broader in thinking and expression. The benefits of environment-based media allow students to better understand natural phenomena that occur in everyday life. Utilization of the environment makes the learning process more meaningful with the outdoor model. Students can explore the natural environment and learn practical skills to understand and appreciate aspects of environmental life. Learning activities will be more interesting for students. In addition, the use of the environment encourages an increase in student learning activities using nature-based learning methods